Yield Trial of Doubled-Haploid Rice Lines with Multiple Abiotic Stress Tolerance - Hayu Widi Yuana; Bambang Sapta Purwoko; Willy Bayuardi Suwarno; Iswari Saraswati Dewi; Cucu Gunarsih (Caraka Tani: Journal of Sustainable Agriculture, 2025)
Rice production is facing a decline due to climate change and land conversion. The development of high-yielding and multi-tolerant abiotic stress rice varieties (such as drought, salinity, and flooding) is needed for adaptation to a changing climate. This research aimed to identify potential doubled-haploid (DH) rice lines with good agronomic performance and high yield through index selection. The study was conducted in the rainy season of 2024, and used a randomized complete block design with a single genotype factor and three replications. The genetic material evaluated consisted of 56 DH rice lines and 5 check varieties, i.e., Inpari 18, Inpari 30, Inpari 34, Inpari 35, and Ciherang. Observation was conducted on plant height (PH), number of vegetative tillers (NVT), number of productive tillers (NPT), days to 50% flowering (DF), days to harvesting (DTH), number of filled grains (NFG), total grains per panicle (TG), panicle length (PL), and productivity. The results showed high heritability in all observed variables, indicating that the variables could be used as selection criteria. The weighted index selection involving PH, NPT, DTH, and productivity resulted in 30 DH rice lines with good agronomic traits such as medium PH, medium NPT, medium maturity, and productivity above the check varieties. Those selected DH lines can be evaluated further in more diverse environments to study the effects of genotype, environment, and G×E interactions.